Mediating Role of Leadership Style on Organizational Citizenship Behavior in the Public Service Sector - Allieu, Sophie; Moriba, Samba (Technium Business and Management, 2023)
This study examined the relationships between transformational and transactional leadership and organizational citizenship behavior in the Public Service Sector of Sierra Leone. While most prior studies have examined transformational leadership-organizational citizenship behavior and transactional leadership-organizational citizenship behavior relationships in developed countries from the western world, testing the mediating inﬂuence of transactional and transformational leaderships on employees’ citizenship behaviors in public sector organizations in Africa remains scarce. It also tries to ﬁll a critical research gap in human resource management by focusing on a non-western context. The constructs: transformational and transactional leadership, organizational citizenship behavior are not very familiar in the human resource research domain in Sierra Leone as opposed to other styles of leadership like Autocratic, Laissez faire etc that are commonly used. Consequently, the broader objective of this research was to examine the links between transformational leadership, transactional leadership, and organizational citizenship behavior at the Public Service Sector in Sierra Leone. To enrich the debate further, this study explored the relationship between transformational and transactional leadership styles and employees’ organizational citizenship behavior. The research questions focused on the correlation between leadership styles and organizational citizenship behavior (OCB). To achieve the objective of the research, a case study research design was used; Quantitative research technique also used; the main variables in the study were used to design a questionnaire in collecting the data: using a sample population of 250 through simple random sampling to conduct this study. This research followed a structural equation model (SEM) approach with validity and reliability tests done to validate the data before testing the hypothesis. The survey planet - a virtual data analysis software was used to analyze the completed online survey items. It has an automated analysis system. The likert scale of 1 to 5 was used to gauge responses from respondents. Statistical analysis method is used for the analysis. Based on the results obtained, the study deduces implications for both theory and practice. Hence, all public service institutions must raise managers' awareness and train them properly so that they can eﬃciently improve and manage the aﬀairs of the institution. Limitations and suggestions for upcoming studies have been discussed.